2023
DOI: 10.3847/1538-4365/ace7c8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Emission Region Properties of Blazars

Junhui Fan,
Hubing Xiao,
Wenxin Yang
et al.

Abstract: Studies and constraints on the emission region are crucial to the blazar radiation mechanism. Yet previous works have mainly focused on individual sources. In this work, we make use of the largest and the latest spectral energy distribution fitting results in the literature to statistically study the blazar emission region properties in the framework of a one-zone leptonic model. Our results reveal: (1) that flat-spectrum radio quasars (FSRQs) show lower electron energy (γ p ≲ 1.6 × 103) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Consequently, a dispersion in δ is not expected to be the main reason for demonstrating the difference in n log sy . In our recent work, Fan et al (2023) estimated B and γ p for blazars with certain classes and they provided lower and upper limits of B and γ p for those BCUs by treating these sources as FSRQs and BL Lacs, respectively. We obtained the values of B and γ p for BCUs using the predicted class assigned by the fractal dimension-inverse discrete wavelet transform method introduced in Cao et al (2024).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a dispersion in δ is not expected to be the main reason for demonstrating the difference in n log sy . In our recent work, Fan et al (2023) estimated B and γ p for blazars with certain classes and they provided lower and upper limits of B and γ p for those BCUs by treating these sources as FSRQs and BL Lacs, respectively. We obtained the values of B and γ p for BCUs using the predicted class assigned by the fractal dimension-inverse discrete wavelet transform method introduced in Cao et al (2024).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the EC process, the cooling process from seed photons, namely ν ext , also plays an important role in determining ν EC . The cooling effect has been counted in the estimation of B and γ p in Fan et al (2023), where we obtained the values of B and γ p for the discussions presented in this work. To sum up, the separation in n log IC between LCP and HCP mainly stems from the dispersion in γ p .…”
Section: Resultsmentioning
confidence: 99%
“…So far, neither the variability timescale nor the SED fitting can yield the distribution of R γ for a larger sample of FSRQs. Therefore, we focus on the large amount of FSRQs recently studied by Fan et al (2023), which obtained the distance from the central black hole to the emission region (R em ) utilizing apparent velocity. The R em of 147 FSRQs was reported, and we identified 134 common FSRQs from our sample ranging from 0.001-21.47 pc with a mean value of 0.88 ± 2.86 pc.…”
Section: Location Of the γ-Ray-emitting Regionmentioning
confidence: 99%
“…These distinctive properties mainly stem from relativistic jets that are closely aligned with our line of sight, typically within a narrow angle of around 10°. Such an alignment results in a pronounced relativistic beaming effect, which significantly amplifies their observed emissions (Blandford & Rees 1978;Angel & Stockman 1980;Abdo et al 2010aAbdo et al , 2010bAcero et al 2015;Ackermann et al 2015;Ajello et al 2020;Zheng et al 2020;Fan et al 2021;Abdollahi et al 2022;Fan et al 2023). According to the rest-frame equivalent width (EW) of emission lines, blazars can be classified as flat-spectrum radio quasars (FSRQs) and BL Lacertae objects (BL Lacs).…”
Section: Introductionmentioning
confidence: 99%
“…Abdo et al (2010a) also divided BL Lac objects into low-frequency peaked (LBLs; e.g., n p S < 10 14 Hz), intermediate-frequency peaked (IBLs; e.g., 10 14 Hz < n p S < 10 15 Hz), and high-frequency peaked (HBLs; e.g., n p S > 10 15 Hz). Many authors (Tavecchio et al 2010b;Zhang et al 2012;Fan et al 2023) have found that the SEDs of BL Lac objects appear to accord with a pure SSC model, especially for HBLs.…”
Section: Introductionmentioning
confidence: 97%